Development of Species-Specific Primers Targeting Mitochondrial Cyt b Gene for Porcine DNA Detection in Halal Authentication via Polymerase Chain Reaction (PCR) - Jekmal Malau; Ahsanal Kasasiah; Aliya Azkia Zahra; Silvana Lestari Irwansyah; Dewi Pratiwi Purba Siboro (Universitas Labuhanbatu, 2025)
Background: The detection of porcine DNA is critical to ensuring adherence to halal standards, particularly in food and pharmaceutical products. This study aimed to design and validate species-specific primers targeting the mitochondrial Cyt b gene of Sus scrofa for porcine DNA identification. Using in silico tools such as NCBI, Primer3Plus, SnapGene, Mega and NetPrimer, four primer pairs were designed and assessed for specificity and efficiency. Methodology: Laboratory validation involved PCR amplification and bi-directional Sanger sequencing. Findings: The findings demonstrated that primers 2F/2R and 3F/3R successfully amplified the target DNA, producing amplicons of 514 bp and 456 bp, respectively. The primers exhibited high specificity, with no amplification observed in non-target DNA samples, including chicken and beef. Sanger sequencing confirmed that the amplified products corresponded to the Cyt b gene sequence of Sus scrofa with 100 % similarity, as validated through BLAST analysis. This study presents an accurate and dependable molecular method for detecting porcine DNA, with valuable applications in halal authentication and molecular diagnostics. Contribution: The developed primers offer an effective tool for accurately identifying porcine-derived components, addressing the critical demand for species-specific DNA detection to support halal compliance.